Waste quantification models for estimation of construction and demolition waste generation: a review - Masudi, A.F.; Che Hassan, C.R.; Mahmood, N.Z.; Mokhtar, S.N.; Sulaiman, N.M. (2012)
Quantification is crucial for construction and demolition waste management. Accurate estimation can be satisfied by developing waste quantification model that is applicable for regional or nation-wide C&D waste generation. This paper presents a review on quantification models for C&D waste from literatures and how they correlate. Most studies combine the empirical waste assessment data or waste generation factor obtained in the field with area of activity level extracted from national statistical database from their respective countries, which provides annual data on sector activities. National or regional estimates provide general figures and forecasts for annual C&D waste generation. Studies found that waste generation factor will differs according to locations. Since volume and characteristic of waste are crucial for waste quantification, quantitative data record from waste audit findings could benefit the authorities for the annual estimates. National C&D waste reduction plan should start from well-established waste minimisation plan at project sites. Copyright Â© 2012 Inderscience Enterprises Ltd.